2017
DOI: 10.1093/cid/cix903
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Immunodeficiency Virus on the Burden and Severity of Influenza Illness in Malawian Adults: A Prospective Cohort and Parallel Case-Control Study

Abstract: Human immunodeficiency virus (HIV)–related immunosuppression is a major risk factor for influenza illness and severity in Malawian adults. Household crowding, food insecurity, and poor sanitation are additional risk factors. Influenza preventive strategies should target HIV-infected adults in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 26 publications
4
30
1
Order By: Relevance
“…In Africa, studies done by Cohen, Walaza (21) reported seroprevalence of 29.8 % in South Africa. Ho, Aston (22) recorded a seroprevalence of 25.4 % in Malawi, similar to that of Ope, Katz (23) that reported an incidence rate of 24.5 % in Kenya. This could be attributed to differences in a lot of factors including sample size and assay type used.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In Africa, studies done by Cohen, Walaza (21) reported seroprevalence of 29.8 % in South Africa. Ho, Aston (22) recorded a seroprevalence of 25.4 % in Malawi, similar to that of Ope, Katz (23) that reported an incidence rate of 24.5 % in Kenya. This could be attributed to differences in a lot of factors including sample size and assay type used.…”
Section: Discussionsupporting
confidence: 68%
“…Our investigation further revealed that 84.1 % (58/69) were IgM seropositive for influenza A while 15.9 % (11/69) were positive for influenza B virus, signifying epidemiological dominance of influenza A over influenza B virus in the third quarter of 2018 in Lagos, Nigeria. Ho, Aston (22) reported that conversely in low resource settings with high HIV prevalence, there is high incidence of influenza illness and greater risk of hospitalization among HIV infected person which explains the high prevalence rate of influenza A detected in this study. A study in Germany recorded higher seroprevalences of 96.3 % for influenza A and 98 % for influenza B using ELISA method, although the study measured IgG antibody in non-HIV patients (17).…”
Section: Discussionmentioning
confidence: 58%
“…Risk factors for influenzaassociated severe illness (e.g. hospitalization or death) have also been assessed using sentinel surveillance systems [23,[25][26][27] and this could be implemented also in Zambia for influenza and other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This study took place in Chikwawa, a rural district in Southern Malawi with an under-five mortality rate of 66 per 1000 live births [25] and a poverty rate of 82% [26]. Chikwawa has a high burden of malaria, schistosomiasis and malnutrition [27][28][29].…”
Section: Study Settingmentioning
confidence: 99%
“…Potential introduction of an influenza vaccination also requires understanding of acceptability, and there is limited evidence on influenza vaccine acceptability within the Malawian context (25). To support effective design and introduction of control strategies, we examined community perceptions and health seeking about influenza and views on influenza vaccination.…”
Section: Introductionmentioning
confidence: 99%